Future Targets in Endometriosis Treatment: Targeting the Endometriotic Implant - Nothnick, Warren B.; Zhang, Xuan (Mini Reviews in Medicinal Chemistry, 2009)
Endometriosis is an enigmatic, debilitating disease which affects as many as 15% of all women of reproductive age and is characterized by pelvic pain and infertility. Current treatment regimes used to manage the disease do so by inducing a hypoestrogenic state. While the absence of circulating estrogen levels lead to a regression of the disease, this hypoestrogenism also induces many unpleasant side-effects. As such, these and other shortcomings of current drug therapies emphasize their limitations and the necessity for the development of novel endometriosis treatments. In this review, current therapies which target the biochemistry of the implant are discussed with emphasis on aromatase inhibitors, antiangiogenic compounds and vascular-disrupting agents.
Keywords: treatment